THE DEVELOPMENT OF THE TRAVEL AND TOURISM INDUSTRY IN THE WORLD - Sofronov, Bogdan (Annals of Spiru Haret University. Economic Series, 2018)
The purpose of this paper is how the travel and tourism industry are changing and development in the world. Travel and tourism industry is one of the world's great industrial sectors. It drives economic growth, creates jobs, improves social development and promotes peace. Hundreds of millions of people around the world are dependent on the sector for their employment. In some island economies, travel and tourism industry is not just the biggest employer, it is effectively the only employer. The role is to contributing to the creation of sustainable economies. Travel and tourism industry is a diverse sector consisting of millions of companies and employers, from the biggest global travel brands to the smallest tour operator or hostel owner. Together we form a formidable force with a voice to be heard at the highest levels of society and government.